2020
DOI: 10.1515/nanoph-2020-0624
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the electron and hole dimensionality to achieve efficient and stable metal halide perovskite scintillators

Abstract: Metal halide perovskites have recently been reported as excellent scintillators for X-ray detection. However, perovskite based scintillators are susceptible to moisture and oxygen atmosphere, such as the water solubility of CsPbBr3, and oxidation vulnerability of Sn2+, Cu+. The traditional metal halide scintillators (NaI: Tl, LaBr3, etc.) are also severely restricted by their high hygroscopicity. Here we report a new kind of lead free perovskite with excellent water and radiation stability, Rb2Sn1-x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…32 The lattice distortion and Jahn-Teller effect make the broad-band emission and large Stokes shift to be observed. The broad-band 560 nm emission, large Stokes shift, and long decay lifetime indicate that 560 nm emission is consistent with the STEs, 43,44 which is similar to the research 45 that has been reported. There is a strong absorption around 200-360 nm observed in the absorption spectra of Rb 2 SnCl 6 , which is attributed to the absorption from 1 S 0 to 1 P 1 .…”
Section: Temperature-dependent Trpl and Its Optical Thermometrysupporting
confidence: 88%
“…32 The lattice distortion and Jahn-Teller effect make the broad-band emission and large Stokes shift to be observed. The broad-band 560 nm emission, large Stokes shift, and long decay lifetime indicate that 560 nm emission is consistent with the STEs, 43,44 which is similar to the research 45 that has been reported. There is a strong absorption around 200-360 nm observed in the absorption spectra of Rb 2 SnCl 6 , which is attributed to the absorption from 1 S 0 to 1 P 1 .…”
Section: Temperature-dependent Trpl and Its Optical Thermometrysupporting
confidence: 88%
“…Generally, a large S means a strong electron–phonon coupling and a high probability of forming STEs. , In our case, S ( ℏω phonon ) of HE and LE emission are calculated to be 7.17 (34.37 meV) and 20.41 (56.87 meV), respectively (Figure d). Obviously, the relatively larger S for LE emission implies a stronger electron–phonon coupling, which mainly originates from the optical phonons.…”
Section: Resultsmentioning
confidence: 60%
“…As for the exploration of scintillators inside the AAO nanopores, the emerging metal halide perovskites (MHP) and their derivatives have attracted our attention due to their remarkable properties such as high quantum yields, tunable emission spectra, large refractive index, facile solution processability, and applicability in nanostructured optoelectronic devices. [16][17][18] Recently, CsPbBr 3 perovskite nanocrystals have been explored as scintillator thin films with high stability, fast response, and high resolution. [19] However, the lateral scintillator light scattering reduces spatial resolution and the severe intrinsic selfabsorption of CsPbBr 3 hinders the light collection efficiency, both of which become severer with increased thickness.…”
Section: Introductionmentioning
confidence: 99%